PENGEMBANGAN PELATIHAN FISIOTERAPI CONTRAST BATH DENGAN MEDIA VIDEO PADA MAHASISWA ILMU KEOLAHRAGAAN - Mustofa, Mustofa; Surendra, Mulyani; Kinanti, Rias Gesang (Jurnal Sport Science, 2014)
Abstract :This study aims to develop a contrast bath with physiotherapy training video media. The results of this development study is expected to make students of Sport Science, State University of Malang more enthusiastic and eager in learning Physiotherapy Sports and Health. The research was conducted at State University of Malang using research and development design by Borg and Gall. The results of this study is a video with the title